The Feasibility of Flipbooks to Elements of the Industrial World and Fashion Development in Fashion Expertise Phase E of SMK N 6 Semarang - Arti Magdalena Sihombing; Wulansari Prasetyaningtyas (Jurnal Penelitian Pendidikan, 2026)
Learning elements in the Basic Fashion Skills Phase E requires contextual and visual digital media. This study aims to test the feasibility of flipbook media as an alternative to interactive learning in the Industrial World and Fashion Development of SMK Negeri 6 Semarang through a quantitative descriptive method. Validation is carried out by material experts and media experts using instruments that have been tested for validity which include aspects of material, language, graphics, and the presentation of material in the media. The results of the analysis with the percentage descriptive analysis technique showed that the feasibility score of material experts was 88.75% and media experts 91.22%, both of which met  the criteria of being very feasible This Flipbook has the potential to be optimal as a supporting medium for vocational learning in fashion after revision, although its effectiveness on student motivation and learning outcomes requires further field trials.